Hygiene and Sanitation Implementation in Kitchen Aston Jember Hotel & Conference Center - Ferdianyah, Ihza Wahyu; Octavy, Syah Riza (Indonesian Journal Publisher, 2024)
The research on the implementation of hygiene and sanitation in the kitchen of the Aston Jember Hotel & Conference Center is presented in this report. In order to make high-quality cuisine, the author of this scientific paper wishes to know what measures are used to preserve kitchen hygiene and sanitation at the Lekker Restaurant Hotel Aston Jember. The author employs a qualitative descriptive research approach to accomplish this goal, which involves performing observations, interviews, and the use of documentation materials. Additionally, the theory of kitchen hygiene and sanitation is combined with other aspects connected to enhancing the quality of these things. The people with power over matters of sanitation and kitchen hygiene were identified as informants for this study. Data from informants, in the form of written or spoken material, was carefully read again, analyzed, and described.